2012
DOI: 10.3389/fncom.2012.00041
|View full text |Cite
|
Sign up to set email alerts
|

Complex dynamics in recurrent cortical networks based on spatially realistic connectivities

Abstract: Most studies on the dynamics of recurrent cortical networks are either based on purely random wiring or neighborhood couplings. Neuronal cortical connectivity, however, shows a complex spatial pattern composed of local and remote patchy connections. We ask to what extent such geometric traits influence the “idle” dynamics of two-dimensional (2d) cortical network models composed of conductance-based integrate-and-fire (iaf) neurons. In contrast to the typical 1 mm2 used in most studies, we employ an enlarged sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 59 publications
1
51
0
Order By: Relevance
“…3). Thus reflects the amount of convergence to a neuron, which is, for instance, consistent with a model of the convergent connectivity from V1 to area V5/MT (Simoncelli and Heeger 1998;Rust et al 2006;Wang et al 2012). In addition, it was observed that the simulation of networks based on biologically realistic parameters (Voges and Perrinet 2010) A: correlation between an noisy Gabor image (input) and a population of Gabor filters at different orientations models the linear processing in the receptive field (RF) of a visual neuron.…”
Section: Overdispersion May Results From Redundancy Within a Neural Pomentioning
confidence: 69%
See 1 more Smart Citation
“…3). Thus reflects the amount of convergence to a neuron, which is, for instance, consistent with a model of the convergent connectivity from V1 to area V5/MT (Simoncelli and Heeger 1998;Rust et al 2006;Wang et al 2012). In addition, it was observed that the simulation of networks based on biologically realistic parameters (Voges and Perrinet 2010) A: correlation between an noisy Gabor image (input) and a population of Gabor filters at different orientations models the linear processing in the receptive field (RF) of a visual neuron.…”
Section: Overdispersion May Results From Redundancy Within a Neural Pomentioning
confidence: 69%
“…could lead to complex dynamics, showing in particular an excess of variability (Voges and Perrinet 2012). Thus we could expect an overdispersion in V5/MT resulting from dimensionality reduction [i.e., projecting inputs from a high-dimensional space to a lower dimensional one (Haykin 1999)].…”
Section: Overdispersion May Results From Redundancy Within a Neural Pomentioning
confidence: 99%
“…In general, neurons in the cerebral cortex are densely connected to neurons close to it and sparsely connected to neurons far away from it (Schummers et al, 2004; Song et al, 2005; Perin et al, 2011; Voges and Perrinet, 2012). In particular, models of cortical function often assume that cortical circuitry acts in a center–surround fashion, whereas separated pairs of cells have a mutually suppressive influence.…”
Section: Methodsmentioning
confidence: 99%
“…The network topology is a key determinant of the types of macroscopic activity patterns a network can generate [4][11]. Understanding this structure-function relationship provides important insight not only into normal brain function but also into the mechanistic basis of psychiatric illnesses such as schizophrenia and autism that likely represent “connectivity disorders” [12][15].…”
Section: Introductionmentioning
confidence: 99%